A super ancient world in pixelated midi: About "Nana de esta pequeña era" by María Salgado and Fran MM Cabeza de Vaca - Trueba Mira, Virginia (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
The purpose of this study is to analyze the audiotext piece, Nana de esta pequeña era by María Salgado and Fran MM Cabeza de Vaca, from the consideration of the intermedial character in which it is articulated, and the political dimension that runs through it. The study starts from a description of the contextual frameworks of the production of the piece; then it goes on to dwell on the modes of inversion of the genre, in the sense that the lullaby does not try in this case to induce sleep but rather to awaken, without losing at the same time the ambivalent character of lullabies, which consists of warding off fear by summoning him. The essay ends with a reflection on the effects of meaning that promotes a syntagm like "little era" to define a time like this. Specific reflections by Gilles Deleuze (on the ritornello) and by Jean-Luc Nancy (on the murmur) will serve to support some of the ideas of this study.